Assessment of Women Studies Specialization in Philippine Normal University: Basis for a New Gender Education Program - Tantengco, Nerissa S; Simeon, Florisa B (ASPENSI, 2015)
ABSTRACT: The study assesses the existing Women Studies Specialization courses offered by the College of Teacher Development thru the Faculty of Behavioral and Social Sciences PNU (Philippine Normal University). This courses will help the university to track down effectively the relevance of subjects taught in Women Studies Specialization as to the number of graduates and employability of graduates. It will also help motivate and transform graduates to be involved in other community advocacies. A descriptive research method was used thru interviews, focused group discussions, and questionnaires. The study used data gathering tools and procedure, such as the questionnaire developed by CHED (Commission on Higher Education), specifically for Tracer Study research. The survey questionnaire was made available to the respondents through the web and the researchers also employed a number of strategies to track the graduates like the use of graduate directory, telephone, mobile phone, social networking sites, look for them in graduate classes during Saturdays, and attending various activities and gathering of the graduates. The study revealed that the graduates of Women Studies Specialization of the Faculty of Behavioral and Social Sciences PNU, from 2003 to 2013, are highly satisfied in the service and learning environment provided by the university; and their acquired skills and competencies during their pre-service were extremely adequate and relevant in current employment.KEY WORD: Women Studies Specialization; Extension Services; Community Advocacies; Undergraduate Courses; Service and Learning Environment.Â RINGKASAN: âPenilaian terhadap Spesialisasi Studi Wanita di Universitas Pendidikan Filipina: Anjakan untuk Program Pendidikan Gender yang Baruâ. Penelitian ini menilai keberadaan kursus Spesialisasi Studi Wanita yang ditawarkan oleh Bagian Pengembangan Guru melalui Fakultas Perilaku dan Ilmu Sosial PNU (Universitas Pendidikan Filipina). Kursus ini membantu universitas untuk melacak secara efektif relevansi kursus yang diajarkan di Spesialisasi Studi Wanita bagi sejumlah lulusan dan pekerjaan lulusan. Ia juga membantu memotivasi dan mengubah lulusan untuk terlibat dalam advokasi masyarakat lainnya. Metode penelitian deskriptif digunakan melalui wawancara, diskusi kelompok terbatas, dan kuesioner. Penelitian menggunakan prosedur alat pengumpulan data, seperti kuesioner yang dikembangkan oleh CHED (Komisi Pendidikan Tinggi), khususnya untuk penelitian karier alumni. Survei kuesioner tersedia bagi responden melalui web dan peneliti juga menggunakan sejumlah strategi untuk melacak lulusan seperti penggunaan direktori lulusan, telepon, ponsel, situs jejaring sosial, mencari mereka di kelas pascasarjana setiap hari Sabtu, dan menghadiri berbagai kegiatan dan pertemuan dengan para lulusan. Studi mengungkapkan bahwa lulusan Spesialisasi Studi Wanita dari Fakultas Perilaku dan Ilmu Sosial PNU, dari tahun 2003 hingga 2013, sangat puas dengan pelayanan dan pembelajaran yang disediakan oleh universitas; serta keterampilan dan kompetensi yang diperoleh mereka selama pra-layanan sangat memadai dan relevan bagi pekerjaan mereka saat ini.KATA KUNCI: Spesialisasi Studi Wanita; Penyuluhan; Advokasi Masyarakat; Sarjana; Layanan dan Lingkungan Belajar.Â Â About the Authors: Prof. Nerissa S. Tantengco, Ph.D. and Assoc. Prof. Florisa B. Simeon, M.A. are the Lecturers at the College of Teacher Development, Faculty of Behavioral and Social Sciences PNU (Philippine Normal University) in Manila, the Philippines. Corresponding authors is: tantengco.ns@pnu.edu.phHow to cite this article? Tantengco, Nerissa S. & Florisa B. Simeon. (2015). âAssessment of Women Studies Specialization in Philippine Normal University: Basis for a New Gender Education Programâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.5(2) December, pp.169-178. Bandung, Indonesia: Minda Masagi Press, ISSN 2088-1290. Chronicle of the article: Accepted (November 28, 2015); Revised (December 12, 2015); and Published (December 30, 2015).